Training on Making Virgin Coconut Oil (VCO) to Increase Income in Friwen Village, Raja Ampat Regency - Siti Nur Azizah (Jurnal Abdi Masyarakat Indonesia, 2023)
In Friwen Village, there is no VCO production yet, even though this village has great coconut potential. Therefore, it requires socialization in the community on how to process coconut into VCO. This activity aims to increase the income of the village community, namely the community in Friwen Village, South Waigeo District, Raja Ampat Regency, West Papua Province. The method used is counseling and the practice of processing diversified coconut-based products. The method for making VCO is fishing, namely by adding some of the finished VCO, which separates the cream of coconut milk from the resulting VCO oil. The results obtained are that partners can produce VCO independently and have knowledge of natural potential that can be utilized to make VCO. After this service, the village community realizes the importance of processing agricultural products to increase income and market their products around the Raja Ampat area.